The Greek-Orthodox Family Structure in the Late Nineteenth Century Sanjak of Kayseri - Celebi, Cagdas Lara (Mediterranean Journal of Social Sciences, 2012)
This study expounds the Greek-Orthodox millet communityâ€™s family formation in the Sanjak of Kayseri in the 1870â€™s from theaspects of especially extended family, polygamy, endogamy, average age of marriage, inheritance rights and ratio of children. Byrevealing heterogeneous tendencies among the Greek-Orthodox communities of different parts of the Ottoman imperial lands, it is partlygoing to be a comparative study. In the same way, while evaluating the Greek-Orthodox family structure, Kayseriâ€™s other sedentarycommunitiesâ€™ family formations â€“Muslim and Armenian one- will be also taken into consideration. Certainly we cannot talk about onetype of family structure, which was assumed as a model and implemented by the Greek-Orthodox inhabitants residing in different partsof the Ottoman domain. In different places, regional factors and local customs seem to play a crucial role in shaping the Greek-Orthodoxfamilies. Like everywhere else in Kayseri too, in addition to these, various socio-economic reasons gave shape to family formation.Comprehension of this subject therefore requires a short examination of such determinant elements. Briefly speaking, in reference toFrederic Le Playâ€™s categorization, the 1870â€™s Kayseriâ€™s Greek-Orthodox families â€“as well as Muslim and Armenian ones- were formed asâ€œstem familyâ€. In the meantime, from the perspective of inheritance rights, they can be defined as a â€œconjugalâ€ family. Likewise,endogamy was also a common feature both in the Muslim and non-Muslim families. Apart from these, we can say that in the vicinity ofKayseri, females and males were prone to marry at early ages.